Application of a Null-Beamformer to Source Localisation in MEG Data of Deep Brain Stimulation - Mohseni, H; Kringelbach, M; Smith, P; Green, A; Parsons, C; Young, K; Brittain, J; Hyam, J; Schweder, P; Stein, J; Aziz, T; IEEE (2010)
In this paper, we present an analysis of magnetoencephalography (MEG) signals from a patient with whole-body chronic pain in order to investigate changes in neural activity induced by DBS. The patient is one of the few cases treated using DBS of the anterior cingulate cortex (ACC). Using MEG to reconstruct the neural activity of interest is challenging because of interference to the signal from the DBS device.We demonstrate that a null-beamformer can be used to localise neural activity despite artefacts caused by the presence of DBS electrodes and stimulus pulses. We subsequently verified the accuracy of our source localisation by correlating the predicted DBS electrode positions with their actual positions, previously identified using anatomical imaging. We also demonstrated increased activity in pain-related regions including the pre-supplementary motor area, brainstem periaqueductal gray and medial prefrontal areas when the patient was in pain compared to when the patient experienced pain relief. © 2010 IEEE.